Analysis of Non-tax Revenue: Evidence from the European Union - Volkan Yurdadoğ; Neslihan Coşkun Karadağ; Murat Albayrak; VolkOğuzhan Bozatlı (Amfiteatru Economic)
The challenges states face in reducing government expenditures under certain budget constraints are putting pressure on states to increase their revenues. Given that taxation also has a limit, the importance of non-tax revenues (NTR) in financing growing government expenditures increases day by day. In this sense, our study first analyzes the historical and theoretical foundations of NTR in the European Union (EU). Subsequently, from 1995 to 2018, NTR's determinants and their interrelationships were analyzed using panel data analysis and panel causality methods. The findings point to statistically significant and robust effects of general and central government expenditures (except local government expenditures), tax revenues, and GDP on the NTR. According to panel causality results, there is unidirectional causality from independent variables (General, Central and Local Government Expenditure, Tax Revenue, GDP) to NTR, and unidirectional causality from NTR to independent variables (except GDP). In other words, there is bidirectional causality between NTR and independent variables, except for GDP.